Impact of Social Media Marketing on Brand Awareness of Watches in Ahmedabad City - Mujiburrehman, Lala; Ravi, Ladumor; Vidani, Jignesh (MultiTech Publisher, 2023)
This study investigates the impact of social media marketing on brand awareness of watches in Ahmedabad city. In an age where digital platforms help shape consumer perceptions, to understand the dynamics of social media marketing's impact on brand awareness becomes critical for a business, such as competing watches. To what extent social media marketing strategies have contributed to the visibility and recognition of the brand in the local market. The research uses a combination of quantitative and qualitative methods to find out. The main purpose of this study is to understand the effectiveness of different platforms to reach and engage the target audience including but not limited to Facebook, Instagram, and Twitter but different social media platforms, etc Focuses and surveys.For brand awareness, social media actions are analyzed to measure the relationship between frequency, type of content shared, and consumer engagement with brand awareness. As such the findings are intended to provide value for the Ahmedabad operating watches brand, which is used to increase their brand visibility and prepare their social media strategy.This study not only contributes to the academic community on the relationship between social media marketing and brand awareness but also provides implications for businesses seeking to optimize digital marketing efforts in the specific context of the watch industry in Ahmedabad city. As consumer behavior is constantly evolving in this digital age, all research marketing strategies should address the timely user reviews that are significant to the success of a watch brand in the local market has the effect